Digitalization in the European agri-food supply chain: a scoping review of traceability, transparency, and sustainability - Bekkouche, Somia; de-Magistris, Tiziana (Frontiers in Blockchain, 2025)
IntroductionMaintaining traceability within the food supply chain is key to ensuring food safety, quality, and regulatory compliance. In recent years, digital technologies—especially blockchain – have been adopted to enhance transparency and trust in ‘farm-to-fork’ traceability systems, reducing fraud risk and enhancing recall management and strengthening consumer trust. However, their adoption differs based on variability in technological readiness, economic viability, and regulatory requirements.MethodsThis paper provides a scoping review of the application of such digital tools to enhance traceability throughout the European agri-food supply chain. being applied across the European agri-food supply chain to improve traceability. Following PRISMA-ScR guidelines, we searched multiple databases (Web of Science, ProQuest, IEEE Xplore, Alcorze) for relevant literature and included 60 peer-reviewed studies (primarily 2010–2025) that met our criteria (focus on blockchain, IoT, AI, or big data in European food supply chain traceability).Results and DiscussionBlockchain emerged as the most frequently studied technology for food traceability —appearing in over 40% of the selected studies —often deployed in combination with IoT sensors, RFID tags, or QR codes to create end-to-end transparency. These digital interventions are reported to strengthen traceability and consumer trust, improve supply chain efficiency, and support sustainability initiatives. However, adoption remains uneven. Most studies describe conceptual frameworks or pilot implementations rather than fully realized systems, and real-world deployment is hampered by interoperability challenges, scalability issues, regulatory uncertainties, and high costs. In conclusion, blockchain-based traceability shows great promise for the European food sector, but targeted efforts are needed to overcome it.Systematic Reviewhttps://archive.org/details/osf-registrations-m34ve-v1.